Pharmacological Actions of Contents of Kabasura Kudineer- A Siddha Formulation for Fever with Respiratory Illness - Kumar, Koppala Narayana Sunil; Divya, Kallingil Gopi; Mattummal, Rubeena; Erni, Bobbili; Sathiyarajeswaran, Parameswaran; Kanakavalli, Kadarkarai (Indian Journal of Pharmaceutical Education and Research, 2021)
Siddha system of medicine is a distinct therapeutic science with many single drugs and compound formulations used for treating a broad spectrum of ailments. Siddha categorizes the fever manifested by viral infestation into 64 types and it has developed medicines for each type. Kapacurak / Kabasurak Kutinir (KK) described in the Citta Vaittiyattirattu is the best promising polyherbal formulation of plant origin for curing viral infections especially with flu-like symptoms. As per Siddha system of medicine Kapacuram is defined as a fever with upper and lower respiratory catarrh. KK is one of the medicines advised for prevention of Coronavirus (COVID-19) outbreak in India by Ministry of AYUSH, Govt. of India. KK also emerged to be a popular traditional medicine for swine flu as well. The current review recapitulates active phytochemicals of all the 15 herbal drug ingredients in KK with the aim to provide it support for usage in flu-like viral infections spreading over the world in the scenario of having no modern medicines. Interestingly, out of 15 herbal ingredients in KK, Zingiber officinale rhizome, Andrographis paniculata whole plant, Syzygium aromaticum flower bud, Cyperus rotundus tuber, Sida acuta roots and Saussurea costus root have been proved to exhibit antiviral activities. All the ingredients have been proved to possess antinflammatory activities. Three proved to have antipyretic potential and five each proved to possess analgesic and immunomodulatory activities. There are ingredients with antiasthmatic and antispasmodic supporting its use in respiratory illnesses such as that caused by COVID-19. The study supports the usage of KK as a traditional Siddha medicine against respiratory illnesses with flu-like symptoms characteristic of SARS-CoV-2.
Keywords: AYUSH; Citta Vaittiyattirattu; COVID-19; Flu-like symptoms; Respiratory; illness; SARS; Traditional medicine